"Make them mature properly": Protective restriction of children from the adult world in China's suburban schools. (17th December 2021) - Zhang, Min
Abstract: The protective restriction of children moving into adulthood has attracted growing attention among the public and experts. This article ethnographically explores how China's suburban teachers practice a selective restriction to help children mature properly. It demonstrates that while educators work to mitigate students' concrete contact with the adult environments, they also inculcate students with the harsh realities of the adult world. It contends that educators' paradoxical attitudes are closely related to the transitional view of childhood in contemporary Chinese society. Consequently, this ideal childhood with appropriate maturity has become a delicate status to achieve and—more importantly—not to overdo.